Indoor Nature Interventions for Health and Wellbeing of Older Adults in Residential Settings: A Systematic Review. (18th March 2019) - Yeo, Nicola L; Elliott, Lewis R; Bethel, Alison; White, Mathew P; Dean, Sarah G; Garside, Ruth
Abstract: Background and Objectives: Having contact with nature can be beneficial for health and wellbeing, but many older adults face barriers with getting outdoors. We conducted a systematic review of quantitative studies on health and wellbeing impacts of indoor forms of nature (both real and simulated/artificial), for older adults in residential settings. Research Design and Methods: Search terms relating to older adults and indoor nature were run in 13 scientific databases (MEDLINE, CINAHL, AgeLine, Environment Complete, AMED, PsychINFO, EMBASE, HMIC, PsychARTICLES, Global Health, Web of Knowledge, Dissertations and Theses Global, and ASSIA). We also pursued grey literature, global clinical trials registries, and a range of supplementary methods. Results: Of 6, 131 articles screened against eligibility criteria, 26 studies were accepted into the review, and were quality-appraised using the Effective Public Health Practice Project (EPHPP) tool. The participants were 930 adults aged over 60. Nature interventions and health/wellbeing outcomes were heterogeneous, which necessitated a narrative synthesis. The evidence base was generally weak, with 18 of 26 studies having a high risk of bias. However, several higher-quality studies found indoor gardening and horticulture programs were effective for cognition, psychological wellbeing, social outcomes, and life satisfaction. Discussion and Implications: There is inconsistent evidence that indoor nature exposures are beneficial for older care residents. We expect that successful interventions were, at least partly, facilitating social interaction, supporting feelings of autonomy/control, and promoting skill development, that is, factors not necessarily associated with nature per se. Higher-quality studies with improved reporting standards are needed to further elucidate these mechanisms.